Dynamics of blackleg epizootic process in the Republic of Kazakhstan - A. Abutalip; B. D. Aitzhanov; A. K. Mussayeva; V. Yu. Sushchikh; N. N. Yegorova; Ye. K. Ospanov; M. A. Berdikulov; K. A. Kalkabayev; N. Matikhan (Ветеринария сегодня)
In 2012–2021, 2,030 outbreaks of acute infectious animal diseases were registered in the Republic of Kazakhstan. Among all the diseases blackleg accounted for 20.7% (421 outbreaks), which suggests that the nosological unit is of high epizootological signiﬁcance among other infectious animal diseases in the country. Analysis of the blackleg outbreaks registered over the recent 10years demonstrates asigniﬁcant annual growth in the number of outbreaks (from19 to 81outbreaks) in the Republic of Kazakhstan and the disease persistence in the territory. Within the mentioned period, the average number of blackleg-infected animals per one outbreak ranged between1 and 3 animals, which proves that blackleg is anon-contagious disease. The research indicates that blackleg is a seasonal disease in the Republic of Kazakhstan with an incidence rise in autumn. The data analysis for 2012–2022 did not reveal any regular blackleg epizooties. The epizootological zoning made it possible to conclude that the blackleg situation in 6 Oblasts (which account for42.8% of the total territory) was rather tense; in 5 Oblasts (35.7% of the country’s territory) the epizootic situation was less tense and the remaining 3 Oblasts (21.5%) are disease-free. Therefore, blackleg zoning in the Republic makes it possible to use a diﬀerential approach to planning preventive veterinary and control measures, depending on the intensity of the epizootic situation. The research results will help to improve the system of blackleg surveillance, to predict the disease spread in animals and can be used to develop anti-epizootic measures.